Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 4 - Proportions, Percents, and Solving Inequalities - Chapters 1-4 Cumulative Review Problem Set - Page 186: 12



Work Step by Step

We substitute $a=3$ and $b=-4$ in the expression and simplify: $2ab-a+6b$ =$2(3)(-4)-(3)+6(-4)$ =$-24-3-24$ =$-51$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.